Organization of the nursing work process in the Hiperdia sector: experience report (Research, Society and Development, 2022)
Objective: To report the experience on the organization of the nursing work process in the Hiperdia sector of a Regional Polyclinic in the city of Niterói R.J. Methodology: This is a descriptive study of experience report type, developed in a Regional Polyclinic in the city of Niterói, carried out in the first half of the year 2022. Results and discussion: The implementation of the work process efficiently, directly implies the quality of service offered to the customer and less margin for error. Thus, it is essential that the nurse manager, in achieving excellence in the services provided, master and articulate theoretical knowledge with practice, assuming their role and being able to make decisions that will ensure a better functioning of the respective sector. The Hiperdia sector is managed by a nurse, whose work activities include planning, communication, qualified assistance, teaching and research. Final considerations: It appears the importance of academic experience in these spaces for understanding the completeness of managerial knowledge, union of theoretical knowledge with practice, awakening a reflective look at the adversities faced by professionals in the exercise of the profession and more enriching training.